THE EFFECT OF LEARNING MODELS MISSOURI MATHEMATICS PROJECT WITH TWO STAY TWO STRAY METHODS FOR MATHEMATICAL PROBLEM SOLVING ABILITY OF STUDENT IN 7 th GRADE SMP N 1 TAWANGMANGU - Rachma Hanan Tiasto; Elly Arliani (Universitas Negeri Yogyakarta, 2016)
AbstractThis study aims to determine the effect of learning models of Missouri Mathematics Project with Two Stay Two Stray methods for mathematical problem solving ability of grade VII students of SMP N 1 Tawangmangu. The method in this study is a quasi experimental research design with pre-test post-test design group. The population in this study were all students of grade VII of State Junior high School 1 Tawangmangu. The sample in this research is grade VII F had treatment with Missouri Mathematics Project learning models of Two Stay Two Stray method as the experimental class and grade VII G as the control class who receive conventional learning treatment. This instrument were tests and observation sheets. The hypothesis test method used was one sample test and t-test independent sample. Based on the results of data analysis, the value of tcount= 7,171 t(0.05:31)=2,0395 with a significance level of 5% thus Ho rejected which means that the learning model of Missouri Mathematics Project with Two Stay Two Stray method was effective in terms of students’ mathematical problem solving ability. The results of data analysis obtained the value of tcount= 6,476 t(0.05:62)=1,998971 thus Ho was rejected. This means that the learning model of Missouri Mathematics Project with Two Stay Two Stray method affected the ability of students' mathematical problem solving.Keywords: Missouri Mathematics Project, Two Stay Two Stray, problem solving ability